PENERAPAN PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN SAINTIFIK BERBANTUAN WORKSHEET GEOGEBRA DAN LKPD DENGAN PENDEKATAN PBL PADA MATERI MATRIKS - Adesia Pradiarti, Refni; Hidayanto, Erry (Jurnal MIPA dan Pembelajarannya, 2024)
The aim of this article describes the results of implementing mathematics learning practices on matrix material using discussion and question and answer learning methods through a scientific approach assisted by GeoGebra worksheet learning media and problem-based LKPD, namely the PBL approach. The model used in practice contains the competencies that students need to have in the 21st century, namely 4C (Creativity, Critical Thinking, Collaboration, and Communication). Based on the results of learning practices related to the Introduction, Core and Closing activities that have been implemented, the use of a scientific approach in learning mathematics on matrix material can provide opportunities for students to widely explore and elaborate on the material studied through the stages of observing, asking questions, gathering information, processing information, and communicating. In addition, using GeoGebra worksheets and LKPD designed using a PBL approach can help students improve their problem-solving skills significantly because students can learn how to identify problems, gather information, and find the right solution to the problems presented.